ANATOMI BATANG DAN DAUN SERTA KANDUNGAN ANTOSIANIN BUNGA PADA TIGA VARIETAS KRISAN (Chrysanthemum spp.) SETELAH MENDAPAT PERLAKUAN PACLOBUTRAZOL - , INTANI QUARTA LAILATY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Paclobutrazol is a kind of plant growth regulators used to suppress plant growth. Its plant regulator could inhibit the synthesis of gibberellins. The application of paclobutrazol in a particular concentration on chrysanthemum has potential on the formation of chrysanthemum pots. The aim of the research was to study the effect of paclobutrazol on the stems and leaves anatomy and anthocyanin content of chrysanthemum (Chrysanthemum spp.). This research was also determine the optimum concentration of paclobutrazol on growth and morphology of plants potted chrysanthemums. The plant variety used were Jaguar red, Snow white and Fiji white. Research was carried out by the application of paclobutrazol concentrations of 0, 50, 100, 150 ppm once in a week for 3 times on three varieties of chrysanthemum. After 8 week growing, the stem and the leaf were prepared for anatomical observation using free hand section and embedding method. Moreover, the chlorophyll content in the leaf and anthocyanin content in the flower were also tested using spectrofotometri. The results showed that the concentration of 150 ppm paclobutrazol increased leaves thickness and stems diameter, as well as the diameter of the trachea. Concentration of 100 ppm paclobutrazol increased cell size of guard cell, palisade and spongy tissue and peripheral tissues. While the concentration of 50 ppm paclobutrazol effect on increasing the number of stomata and pith diameter. Giving to the concentration of 150 ppm paclobutrazol could increased levels of anthocyanin in the all flower varieties. The optimum concentration of paclobutrazol to form a potted chrysanthemum was 150 ppm.